Quad-Band Terahertz Metamaterial Absorber Based on the Combining of the Dipole and Quadrupole Resonances of Two SRRs - Wang, Ben-Xin (IEEE journal of selected topics in quantum electronics, 2017)
A new type of quad-band terahertz metamaterial absorber based on a common sandwich structure is investigated. In sharp contrast to the most previous studies focused on only combining of fundamental resonance (or LC resonance) of the metamaterial structure to obtain the quad-band response, we directly enable near-unity absorption in four distinct peaks by utilizing the dipole and quadrupole resonances of the patterns. The design also has the ability to tune the frequencies of the absorption peaks by merely changing the angle of polarization. The proposed platform has potential application perspectives in imaging, sensing, and detection.